Outcome of tendon transfer for radial nerve palsy in Misrata (Journal of Academic Research, 2026)
Background: Radial nerve palsy can result in significant functional limitations, including wrist and finger drop, impairing daily activities and work capacity. Tendon transfer is a well-established surgical approach to restore motor function in patients with irreversible radial nerve injury.Objective: To evaluate the short-term functional outcomes of tendon transfers in patients with high radial nerve palsy in northwest Libya using a comprehensive assessment protocol.Methods: A prospective study was conducted between 2021 and 2024 including 20 patients (17 high, 3 low radial nerve palsy) with chronic radial nerve injuries. Tendon transfers performed included pronator teres to extensor carpi radialis brevis (wrist extension), palmaris longus to extensor pollicis longus (thumb extension/abduction), and flexor carpi radialis to extensor digitorum communis (finger extension). Postoperative rehabilitation included splinting and physiotherapy. Outcomes were evaluated using the modified DASH score and Bincaz scoring system.Results: The mean age was 36 years (range 16–56). Postoperative DASH scores improved significantly (mean pre-op 48 → mean post-op 18 at 10 weeks). According to Bincaz scoring, 3 patients achieved excellent outcomes, 15 good, and 2 poor. Complications were minimal and included radial deviation of the wrist (n=2), restricted wrist flexion (n=2), and thumb abduction deficiency (n=2). Overall, 95% of patients returned to their normal daily activities within 8 weeks.Conclusion: Tendon transfers for radial nerve palsy provide reliable restoration of wrist, finger, and thumb function, with high patient satisfaction and early return to daily activities. This surgical approach effectively transforms a drooping hand into a functional and efficient unit.
Keywords: Radial nerve palsy; tendon transfer; wrist extension; finger extension; thumb function